Thermally Reconfigurable Meta-Optics - Tomer Lewi; Nikita A. Butakov; Hayden A. Evans; Mark W. Knight; Prasad P. Iyer; David Higgs; Hamid Chorsi; Juan Trastoy; Javier Del Valle Granda; Ilya Valmianski; Christian Urban; Yoav Kalcheim; et al. (IEEE Photonics Journal)
Metasurfaces are two-dimensional nanostructures that allow unprecedented control of light through engineering the amplitude, phase, and polarization across meta-atom resonators. Adding tunability to metasurface components would boost their potential and unlock a vast array of new application possibilities such as dynamic beam steering, tunable metalenses, and reconfigurable meta-holograms, to name a few. We present here high-index meta-atoms, resonators, and metasurfaces reconfigured by thermal effects, across the near to mid-infrared spectral ranges. We study thermal tunability in group IV and group IV–VI semiconductors, as well as in phase-transition materials, and demonstrate large dynamic resonance frequency shifts accompanied by significant amplitude and phase modulation in metasurfaces and resonators. We highlight the importance of high-Q resonances along with peak performance of thermal and thermo-optic effects, for efficient and practical reconfigurable devices. This paper paves the way to efficient high-Q reconfigurable and active infrared metadevices.